2021
DOI: 10.7717/peerj.10693
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence, prevalence and years lived with disability of facial fracture at global, regional and national levels from 1990 to 2017

Abstract: Background Facial fracture is one of the most common injuries globally. Some types of facial fractures may cause irreversible damage and can be life-threatening. This study aimed to investigate the health burden of facial fractures at the global, regional, and national levels from 1990 to 2017. Methods Facial fracture data, including the incidence, prevalence, and years lived with disability (YLDs) from 1990 to 2017, were obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…HPASD promoted cartilage callus formation and osteogenesis initiation, as accompanied by upregulated expression levels of RUNX2, Smad1/5/9, EP4, ERK1/2, RSK2, and ATF4 in a time-dependent and concentration-dependent manner in chondrocyte-specific BMP2 knockout mice. Overall, our findings demonstrated that HPASD induced COX2 transcription through the 1…”
supporting
confidence: 56%
See 1 more Smart Citation
“…HPASD promoted cartilage callus formation and osteogenesis initiation, as accompanied by upregulated expression levels of RUNX2, Smad1/5/9, EP4, ERK1/2, RSK2, and ATF4 in a time-dependent and concentration-dependent manner in chondrocyte-specific BMP2 knockout mice. Overall, our findings demonstrated that HPASD induced COX2 transcription through the 1…”
supporting
confidence: 56%
“…One of the main causes of death and disability worldwide is fracture, a common clinical illness. 1,2 Traumatic brain injury (TBI) patients with fractures recover more quickly than patients with simple fractures and even exhibit heterotopic ossification, according to research on the clinical treatment of fractures. 3 However, uncertainty persists regarding the precise mechanism by which TBI accelerates fracture repair.…”
Section: Introductionmentioning
confidence: 99%
“…The facial region is the most visible among the body parts, delicate in structure, and lacks protection [ 44 , 52 ], resulting in it being the leading cause of morbidity [ 32 , 43 ]. The high incidence and financial cost of treatment and rehabilitation and the possibility of the devastating irreversible damage that might result from a facial injury have made it a significant challenge for public healthcare services [ 7 , 15 , 53 ]. Hence, this invariably inflicts a substantial economic burden on the national health budgets, further constraining the present delicate health systems in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Markedly, low- and middle-income countries (LMICs) accounted for 89% of the deaths, while 10% were attributed to sub-Saharan Africa (SSA) [ 5 , 6 ]. Maxillofacial injury (MI) is categorized as a nature of injury [ 6 ] and is characterized by the injury that may result in damage to soft and hard tissues of the facial region in the form of burns, lacerations, and fractures [ 7 , 8 ]. The fractures that entail the orbits, maxillary, nasal, mandible, and other bones in the facial region [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The 2017 Global Burden of Disease study showed that the global number of facial fracture cases increased from 5405,814 in 1990-7538,663 in 2017, an increase of 39.45%. 2,3 Furthermore, maxillofacial nerves and muscles, multiple and complex, are positioned near the maxillofacial bones. Fractures of the maxillofacial bones may have serious functional and cosmetic sequelae, and have adverse effects on the patient's quality of life, psychological wellbeing, and social interactions.…”
mentioning
confidence: 99%